The Influence of Self-Efficacy and Self-Regulated Learning on Students' Motivation to Learn Mathematics - Sulthon Zulkarnain Siregar; Isran Rasyid Karo-Karo S; Siti Salamah Br Ginting (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research aims to analyze the influence of self efficacy and self regulated learning on students’ motivation to learn mathematics. The research employed a quantitative approach with a correlational design. The participants were 42 senior high school students selected using a purposive sampling technique. A questionnaire was used to measure self efficacy, self regulated learning, and mathematics learning motivation. Data were analyzed using simple and multiple linear regression with the assistance of SPSS software.The results showed is self efficacy had a positive and significant effect on students’ mathematics learning motivation, self regulated learning had a positive but not significant effect on mathematics learning motivation and self efficacy and self regulated learning jointly had a significant effect on mathematics learning motivation, whereas partially, only self efficacy showed a positive and significant effect. In contrast, self regulated learning did not make a significant contribution, although its influence remained positive.